2016
DOI: 10.4236/ojepi.2016.61001
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Defaulters from Tuberculosis Treatment in a Tertiary Hospital in South Eastern Nigeria

Abstract: Background: Tuberculosis is second only to HIV/AIDS as the greatest killer worldwide, due to a single infectious agent. Directly Observed Treatment Short-Course (DOTS) is presently the WHO recommended programme to fight tuberculosis worldwide. There is a need to understand the characteristics of patients who default from treatment for tuberculosis. This will help modify the strategies to reduce such default to the barest minimum and achieve higher levels of adherence. Objective: The aim of this study was to de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
9
5

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 7 publications
5
9
5
Order By: Relevance
“…This report was in line with findings from some of the reviewed works [5] [6] [19] [29] [52]. It has been globally reported that TB occurs mostly as pulmonary types in greater than 80% of all cases [5] [6].…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…This report was in line with findings from some of the reviewed works [5] [6] [19] [29] [52]. It has been globally reported that TB occurs mostly as pulmonary types in greater than 80% of all cases [5] [6].…”
Section: Discussionsupporting
confidence: 90%
“…It was also lower than figures reported from studies in Ekiti state Nigeria, (93.0%) [55], Turkey (94.7%) [43], India, (84.6%) [7] and also below the national recommended target of June 2016 | Volume 3 | e2754 85% [14]. Nevertheless, the treatment success found in this study was higher than figures reported in studies from, Nnewi, (61.3%) [19] Owo Ondo state, (75.5%) [51] Ibadan (76.6%) [17], Ebonyi state, (65.8%) [40], Abuja, (65.8%) [39] all from Nigeria and in Limpopo South Africa, (74.4%) [25]. Yet our findings compares favorably with the treatment successes reported in some other studies; 82% from a study in Enugu state [49], 80% in another study from Ebonyi state [56], 83.4% in India [26] and 82.7% in Addis Ababa, Ethiopia [23].…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations